2(t-3)=4(t+2)

Simple and best practice solution for 2(t-3)=4(t+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(t-3)=4(t+2) equation:


Simplifying
2(t + -3) = 4(t + 2)

Reorder the terms:
2(-3 + t) = 4(t + 2)
(-3 * 2 + t * 2) = 4(t + 2)
(-6 + 2t) = 4(t + 2)

Reorder the terms:
-6 + 2t = 4(2 + t)
-6 + 2t = (2 * 4 + t * 4)
-6 + 2t = (8 + 4t)

Solving
-6 + 2t = 8 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-6 + 2t + -4t = 8 + 4t + -4t

Combine like terms: 2t + -4t = -2t
-6 + -2t = 8 + 4t + -4t

Combine like terms: 4t + -4t = 0
-6 + -2t = 8 + 0
-6 + -2t = 8

Add '6' to each side of the equation.
-6 + 6 + -2t = 8 + 6

Combine like terms: -6 + 6 = 0
0 + -2t = 8 + 6
-2t = 8 + 6

Combine like terms: 8 + 6 = 14
-2t = 14

Divide each side by '-2'.
t = -7

Simplifying
t = -7

See similar equations:

| 24=7x-6-2x | | .2=62 | | 15k+5=5(2x-3) | | -8(4+v)=64 | | 3x-9=3(-3+1x) | | 2x+4+x=4x+4-x | | 8x^2+22x-76=0 | | 62=.2 | | 5d-8=5(1d+3) | | p(t)=-2t^2+5t+8 | | 2a+b=-16 | | 5(-7x+3)=-265 | | 6n+3(8n+5)=255 | | 2xy-6y= | | 9y-2(y+14)=84 | | 5(13-9)-10(5+11x)=170 | | 3(7-8n)-4=-103 | | -18=8-6k-8 | | 4ab-5b= | | 6x-9y=25 | | 9x^2-4y^2-36x-24y+36=0 | | x^2+2.86x-21428.57=0 | | -41=x+88 | | Y=3x^2-9x+18 | | 2y-25=19 | | 0=-7x-2x | | Ax+7=bx+8 | | y-(-2)=8(x-(-2)) | | -7=.2+m | | A=mnp | | 5.8(x-4)=0.2x+6.8 | | 10-3y=7y+2 |

Equations solver categories